Analisis Pengaruh Disiplin Pengendara, Penegakan Hukum, Kondisi Motor dan Jalan Terhadap Keselamatan Berlalu Lintas: Studi Kasus Pengendara Roda Dua di Jl Raya Kudus Pati - Saputro, Dicky Febri Ragil; Roesjanto, Roesjanto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Traffic safety is influenced by several factors including Driver Discipline, Law Enforcement, Motorcycle and Road Conditions. Of the three, have an important role in improving traffic safety with satisfactory results. The purpose of this study was to determine whether or not there is an effect of Driver Discipline, Law Enforcement, Motorcycle and Road Conditions on Traffic Safety on Jl. Holy-Pati Raya In this study, the research population is Traffic Safety on Jl. Raya Kudus-Pati with a sampling system with a total of 100 respondents (sample). The variables in this study consist of: the independent variable is Driver Discipline (X.1), Law Enforcement (X.2), and Motorcycle and Road Conditions (X.3) and the dependent variable is Traffic Safety (Y). The research model is multiple linear regression analysis. The results of the analysis with statistical tools SPSS V.16 program obtained multiple linear regression equation Y = 2.758 + 1.963 X1 + 0.171 X2 + 0.287 X3+ µ . The results of the multiple linear equations show that there is a positive and significant influence between Driver Discipline on Traffic Safety (t count 13.675> t table 1.98447), Law Enforcement on Traffic Safety (t count 1.292 > t table 1.98447), Motor and Road Conditions on Traffic Safety (t count 2.099 > t table 1.98447), individually, Rider Discipline, Law Enforcement, Motorcycle and Road Conditions affect Traffic Safety. The influence of the three research variables is very strong with the coefficient value (R Square) obtained by 71% on Traffic Safety and 29% is influenced by variables that are not detected in this study.